Dispersal has inhibited avian diversification in Australasian archipelagoes - Weeks, Brian C. (The Royal Society, 2014)
Different models of speciation predict contrasting patterns in the relationship between the dispersal ability of lineages and their diversification rates. This relationship is expected to be negative in isolation-limited models and positive in founder-event models. In addition, the combination of negative and positive effects of dispersal on speciation can result in higher diversification rates at intermediate levels of dispersal ability. Using molecular phylogenies to estimate diversification rates, and wing morphology to estimate dispersal ability, we analysed the influence of dispersal on diversification in the avifauna of Australasian archipelagoes. Contrary to expectations given the fragmented nature of island systems, the relationship between dispersal ability and diversification rate was monotonically negative. While multiple mechanisms could generate this pattern, they all share a phase of range expansion that is decoupled from speciation.